ANALYSIS OF STUDENTS’ COMMUNICATION STRATEGIES IN ESP CLASS OF MATHEMATIC STUDY PROGRAM - Rizky Ayuningtyas; Hery Yufrizal (Bandar Lampung University (UBL), 2016)
This study examines communication strategies mostly appeared during the learning process at an ESP class, the code switch occurred during the presentation, and the meaning of the code switch that the students used. This research was non experimental descriptive study. Samples in this study were 20 fresh college learners of mathematic study program in a class at University of Lampung. The results show that of the 12 Communications Strategies (CSs) available, the students used 9 CSs. The researcher divided CSs that is used by the students into 4 levels, High frequency strategies (code switching (36,28%), time-gaining strategies (30,37%), and appeal for help (16,03%)), Mid frequency strategies (non-linguistic signal (6,32%) and literal translation (4,64%)), low frequency strategies (message abandonment (2,53%), topic avoidance (2,11%), circumlocution (0,84%), and approximation (0,84%)), non existence strategies (use of all purpose words, word coinage, and foreignizing).